Influence of Mo and Al elements on the vacuum high temperature tribological behavior of high strength nickel alloy matrix composites. (March 2019) - Zhen, Jinming; Han, Yunxiang; Chen, Jiao; Cheng, Jun; Zhu, Shengyu; Yang, Jun; Kong, Lingqian
Abstract: Vacuum along with high temperature is typical service condition for machinery components operated in aerospace. In this paper, the effects of Al and Mo elements on the mechanical and vacuum tribological properties of the nickel-alloy matrix solid-lubricating composites were investigated. Results presented that the increased addition of Al element noticeably improved the wear resistance and mechanical properties of the composites due to the formation of intermetallic in composites. While increasing content of Mo element means higher Vickers hardness and lower wear rate at low and moderate temperatures. The wear mechanism was proposed based on microstructure and compositions of sliding surface. Highlights: Four nickel-alloy matrix composites with different content of Mo were prepared. The tribological properties in vacuum from RT to 800 °C were investigated. The COF and wear rate were quite dependent on the temperature. Addition of Mo element increase solid-solution strengthening from RT to 600 °C.